2009
DOI: 10.1186/1475-2840-8-29
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin genotype is a determinant of survival and cardiac remodeling after myocardial infarction in diabetic mice

Abstract: Background: We have recently demonstrated in man that a functional allelic polymorphism in the Haptoglobin (Hp) gene plays a major role in determining survival and congestive heart failure after myocardial infarction (MI). We sought to recapitulate the effect of Hp type on outcomes and cardiac remodeling after MI in transgenic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…24 This suggests that the Hp 2-2 phenotype is associated with an increased risk of atherosclerotic cardiovascular disease. In a recently published study of diabetic transgenic mice, 25 it was found that the Hp 2-2 phenotype was associated with increased mortality and more severe cardiac remodeling 30 days after myocardial infarction. In addition, Hp 2-2 has been associated with refractory hypertension, 26 is a predictor of diabetic nephropathy, 27 is associated with a higher risk of mortality in tuberculosis, 28 and a lower hepatitis B level 29 than other phenotypes.…”
Section: Discussionmentioning
confidence: 98%
“…24 This suggests that the Hp 2-2 phenotype is associated with an increased risk of atherosclerotic cardiovascular disease. In a recently published study of diabetic transgenic mice, 25 it was found that the Hp 2-2 phenotype was associated with increased mortality and more severe cardiac remodeling 30 days after myocardial infarction. In addition, Hp 2-2 has been associated with refractory hypertension, 26 is a predictor of diabetic nephropathy, 27 is associated with a higher risk of mortality in tuberculosis, 28 and a lower hepatitis B level 29 than other phenotypes.…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, the presence of Hp-2 is linked to diabetes-related cardiovascular disease in addition to other conditions. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Others found that the Hp genotype was associated with both nephropathy 38 and cardiovascular risk. 39,40 Ophthalmologic studies focusing on diabetic retinopathy in murine models 41,42 and humans 43 suggested that the Hp-2 genotype plays a provocative role.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in a nested control study de Bacquer et al showed that Hp 1-1 patients had a higher risk of IHD compared to Hp 2-2 and Hp 2-1 patients [39]. Studies on CVD and Hp genotype in diabetes show more consistent results, both in human studies [21] and recently in a mouse model [40]. Levy et al demonstrated in the Strong Heart study [20] that Hp 2-2 is a major predictor of CVD in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%